FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP SEMARANG SELATAN - Mega Dresti Rarastya Nugraheni; Ceacilia Srimindarti (KRISNA: Kumpulan Riset Akuntansi, 2022)
This study aims to determine the effect of taxpayer awareness on taxpayer compliance, tax knowledge on taxpayer compliance, service quality on taxpayer compliance and tax sanctions on taxpayer compliance. This research is a quantitative research with the number of respondents as many as 100 respondents who are taxpayers at KPP South Semarang. Data obtained by distributing questionnaires directly. The sampling technique used is accidental sampling. The data used are primary data in the form of respondents' answers and processed using SPSS 23. The results show that taxpayer awareness has a positive and significant effect on taxpayer compliance, tax knowledge has a positive and significant effect on taxpayer compliance, service quality has a positive and significant effect on taxpayer compliance. taxpayer compliance, tax sanctions have a positive and significant effect on taxpayer compliance.